Effect of Vegetable-Based Nanofluid Enriched with Nanoparticles as Metalworking Fluids During Orthogonal Cutting Process - Norfazillah, Talib; Ainaa Mardhiah, Sabri; Nor Athira, Jamaluddin; Mohamad Hafiz Akmal, Suhimi; Amiril Sahab, Abdul Sani (Springer Nature, 2022)
The growing interest in the usage of vegetable oils as a based fluid for the lubrication industry led to more study on the potential of vegetable oils as MWFs to replace the mineral-based oil due to the environmental benefits such as renewable and biodegradable. In this study, vegetable-based nanofluids were formulated from modified jatropha oils (MJO) mixed with nanoparticle additives copper oxide and activated carbon at different concentration of 0.01, 0.025 and 0.05wt.%. The aim of this study was to evaluate the machining performance of the nanofluids (MJOc1, MJOc2, MJOc3, MJOa1, MJOa2 and MJOa3) compared with the commercial synthetic ester (SE)in terms of cutting temperature and chip thickness. The lathe machine (Harrison alpha 400) was used for orthogonal cutting with the minimum quantity lubrication (MQL) method. Thermal imager camera FLIR T640 used in this experiment to measure the maximum cutting temperature by placing the camera in an axial direction during the machining process. Then, a micrometre (model: Mitutoyo IP 65) used in this experiment to measure the chip thickness while a tool maker measuring microscope used to measure the tool chip contact length after the experimental process. MJO with nanoparticle additions has the potential to replace SE as a long-term metalworking fluid.